Evaluation of a Continuing Professional Development program for first year student pharmacists undergoing an Introductory Pharmacy Practice Experience - Toyin Tofade, MS, PharmD, BCPS, CPCC, Pharmacotherapy Director, Wake Area Health Education Center and Clinical Associate Professor, Division of Pharmacy Practice and Experiential Education; Brianna Franklin, student, fourth professional year; Bennett Noell, student, fourth professional year 1; Kim Leadon, MEd, Clinical Assistant Professor and Director of Experiential Education, Division of Pharmacy Practice and Experiential Education (INNOVATIONS in Pharmacy, 2011)
Objectives: The purpose of the study was to evaluate a live and online training program for first year pharmacy students in implementing Continuing Professional Development (CPD) principles (Reflect, Plan, Act, and Evaluate), writing SMART learning objectives, and documenting learning activities prior to and during a hospital introductory professional practice experience.Design: Cohort Study. Setting: Introductory professional practice experience. Participants: First year (PY1) students at the University of North Carolina Eshelman School of Pharmacy. Intervention: Live training or online training to introduce the concept of Continuing Professional Development in practice. Main Outcomes: Implementation of CPD principles through 1) completed pre-rotation education action plans with specific, measurable, achievable, relevant and time-bound (SMART) learning objectives; and 2) completed learning activity worksheets post-rotation indicating stimuli for learning, resources used and accomplished learning. objectives; and 3) documented suggestions and content feedback for future lectures and pharmaceutical care lab experiences. Results: Out of the whole cohort (N=154), 14 (87.5%) live (in person) trainees and 122 (88%) online trainees submitted an education action plan. Objectives were scored using a rubric on a scale of 1-5. A rating of 5 means “satisfactory”, 3 means “work in progress” and 1 means “unacceptable”. There were significant differences between the mean live trainee scores and the mean online trainee scores for the following respective section comparisons: Specific 4.7 versus 3.29 (p<0.001); Measurable 3.9 versus 2.05 (p<0.001); number of objectives 3.6 versus 4.6 (p<0.001); and average grade 92.9 versus 77.7 (p<0.001). Of the 396 learning activity worksheets reviewed, 75% selected discussion with peers and/or health providers as a stimulus for learning. Students reported spending an average of 50.2 hours completing the learning objectives. All of the pre-stated objectives were fulfilled completely or partially. Conclusion: Live trainees performed significantly better than online trainees in writing SMART learning objectives. With focused training, students are more capable of implementing principles of CPD.